2018
DOI: 10.1039/c7tc04795a
|View full text |Cite
|
Sign up to set email alerts
|

The surface chemistry of iron oxide nanocrystals: surface reduction of γ-Fe2O3 to Fe3O4 by redox-active catechol surface ligands

Abstract: The effect of surface functionalization on the structural and magnetic properties of catechol-functionalized iron oxide magnetic (γ-Fe2O3) nanocrystals was investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 51 publications
0
21
0
Order By: Relevance
“…Also, post-synthesis surface-functionalization can affect phase distribution, as demonstrated by Daniel and co-workers [60]. The replacement of oleic acid by catechol surface ligands led to the separation into two distinctive magnetic entities, due to reduction of a nanoparticle surface fraction to magnetite, which reduced the anisotropy constant and, consequently, the effective magnetization [60].…”
Section: Synthesis Of Shape Anisotropic Nanoparticlesmentioning
confidence: 99%
“…Also, post-synthesis surface-functionalization can affect phase distribution, as demonstrated by Daniel and co-workers [60]. The replacement of oleic acid by catechol surface ligands led to the separation into two distinctive magnetic entities, due to reduction of a nanoparticle surface fraction to magnetite, which reduced the anisotropy constant and, consequently, the effective magnetization [60].…”
Section: Synthesis Of Shape Anisotropic Nanoparticlesmentioning
confidence: 99%
“…10 When Fe 3 O 4 and γ-Fe 2 O 3 coexist, they will exhibit better stability, magnetic properties, and catalytic properties. 11 However, one extremely important point cannot be ignored that the efficiency of mono iron oxides at low temperature (<300 °C) is not high. 11,12 Catalysts that contain CuO species have been identified as active substances for the reduction of NO by CO. 12,13 However, it was found that single copper oxide still exhibited a lower NO reduction activity at low temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure a, ligand exchange with DHCA was verified by Fourier transform infrared (FTIR) spectroscopy . The magnetic nanoparticles covered with oleic acid showed strong CH 2 peaks at 2,921, 2,850, and 1,420 cm −1 before modification.…”
Section: Resultsmentioning
confidence: 85%